The Immune Cells in Adipose Tissue - Ferrante, Anthony W. (2013)
Although the pathological role of the immune system in several metabolic disorders, including type 1 diabetes mellitus (T1DM) and Addison’s disease, has long been recognized and studied, only in the last decade has it become apparent that the immune system plays a broad and more subtle role in local and systemic metabolism. It is now apparent that the immune system monitors and responds to specific metabolic cues in both pathologic and non-pathologic settings through a set of processes dubbed immunometabolism. Expansion of adipose tissue mass, activation of lipolysis, eating a high fat diet and even non-shivering thermogenesis all lead to the recruitment and activation of immune cells in key metabolic tissues. The responses are complex and not completely defined, and indeed, as is typical of rapidly evolving research areas, there are some conflicting reports, especially related to the metabolic consequences of manipulation of immune function. However, what is clear is the consensus that metabolic processes, especially obesity and obesity-related complications, activate both the innate and adaptive arms of the immune system. Canonical immune processes consist of discrete steps: surveillance, recognition, effector action and resolution. Over the last decade evidence for each part of the immune response has been found at the intersection of the immune system with metabolism. Although evidence for immune surveillance and modulation of metabolism has been found in the liver, muscle, hypothalamus and pancreas, immune cell function has been most intensively studied and best understood in adipose tissue where studies continue to provide insights into the intersection of the metabolic and immune systems. Here we review the modulation of immune cell populations in adipose tissue and discuss regulatory processes implicated in controlling the interface between metabolism and immunologic function.